Effects of pH on salicylic acid toxicity in terms of biomarkers determined in the marine gastropod Gibbula umbilicalis. (June 2020) - Dionísio, Ricardo; Daniel, David; Arenas, Francisco; Campos, João C.; Costa, Paulo C.; Nunes, Bruno; Correia, Alberto Teodorico
Abstract: Alterations of the physical-chemical properties of the oceans due to anthropogenic activities are, at present, one of the most concerning environmental issues studied by researchers. One of these issues is ocean acidification, mainly caused by overproduction and release of carbon dioxide (CO2 ) from anthropogenic sources. Another component of environmental degradation is related to the production and release of potential toxic compounds, namely active pharmaceutical ingredients, into the aquatic environment that, combined with oceanic acidification, can cause unpredictable and never before considered deleterious effects on non-target marine organisms. Regarding this issue, the hereby study used predictions of future ocean acidification to simulate realistic scenarios of environmental exposure to a common therapeutic drug, salicylic acid (SA), in the marine gastropod Gibbula umbilicalis under different pH values. This species was exposed to a range of pH values (8.2, 7.9 and 7.6), and to already reported environmentally realistic concentrations (5, 25 and 125 μg/L) of SA. To evaluate the effects of these environmental stressors, key physiological biomarkers (GSTs, CAT, TBARS, AChE and COX) and shell hardness (SH) were quantified. Results from the present study showed that CAT and GSTs activities were enhanced by SA under water acidification; increased lipid peroxidation was also observed in organisms exposed to SA in more acidic media. In addition, the hereby study demonstrated the neurotoxic effects of SA through the inhibition of AChE. Effects were also observed in terms of COX activity, showing that SA absorption may be affected by water acidification. In terms of SH, the obtained data suggest that SA may alter the physical integrity of shells of exposed organisms. It is possible to conclude that the combination of seawater acidification and exposure to toxic xenobiotics (namely to the drug SA) may be strenuous to marine communities, making aquatic biota more susceptible to xenobiotics, and consequently endangering marine life in an unpredictable extent. Highlights: Physiological alterations were enhanced under SA exposure at lower pH levels. Lipid peroxidation increased after seawater acidification. Neurotoxic effects were reported under SA exposure. Prostaglandins biosynthesis pathway inhibited by SA absorption at lower pH levels.